Gathering in a cyber world: Internet use of Chinese disabled people and the emergence of disability constituencies. Issue 7 (14th September 2019) - Qu, Yuanyuan; Watson, Nicholas
Abstract: This article examines how Chinese disabled people use the Internet to create active constituencies and the potential for this to afford the opportunity for a new form of activism. Based on a content analysis of China's two largest disability online forums, the article documents disabled people's online activities. These include the description of everyday activities, the build-up of social relations, and organisation and mobilisation for changes. The analysis suggests the emergence of new disability constituencies. This, the article argues, is starting to reshape dis-ability politics and develop new disability activism.